APPLICATION OF HARDWARE CAPITAL THERAPY TO IMPROVE THE QUALITY OF LIFE WITH HYPERTENSION IN THE AREA OF PUSKESMAS ROWOSARI SEMARANG - Margiyati, Ns. Margiyati; Awaliyah Luthfiyah (Pusat Riset dan Inovasi Nasional, 2021)
Elderly is a population at high risk of impaired cognitive function.Reduced memory, intellectual function and the ability to learn are changes in cognitive function that can reduce the quality of life of the elderly. Playing “Remi” card is one of the non-pharmacological therapies that can improve cognitive function in the elderly. Types of research used is descriptivewith a case study debiting method. The subjects used were 2 people with criteria aged 60-74 years, not color blind , not illiterate, can sit. Measurement of cognitive function using Mini Mental State Examination (MMSE). Intervention playing “remi” card games with the method of “tepuk nyamuk”for 5x meetings in 2 weeks. The results of the analysis, subject Iincreased from a score 23 to 27, subject II from a score of 26 to 28. The results of the case study concluded that there was an increase that reaching 8.66 cognitive function. “Remi” cards game with the method “tepuk nyamuk” is recommended as a nursing intervention in the management of cognitive enhancement function in elderly.